Desktop-Based Savings and Loans Data Information System at the Dana Mandiri Syariah Lambaro Cooperative - Nanda Mansyura (STMIK Indonesia Banda Aceh, 2023)
The savings and loan information system at the Dana Mandiri Syariah Cooperative is a business entity that operates in the savings and loans sector, where data processing still uses Miscrossoff Excel or bookkeeping, so it is less effective and efficient. Therefore, the author here takes the problem in the field of savings and loan data itself. By creating a more effective and efficient system, namely the xampp system, it is hoped that it can help cooperatives to improve services more quickly, as well as to store data or other important documents that must be stored properly so that the presentation of information is relatively fast and accurate. The savings and loans information system development method was created using the prototype method using system development tools in the form of Flow maps (Document flow charts), context diagrams (Contex Diagrams), DFDs (Data Flow Diagrams) and design tools, the proposed database is in the form of ERD ( entity relationship diagram) table relationships. As well as data collection techniques using research methods by means of observation, interviews and data collection. Program implementation uses a desktop programming language with a database using xampp. The savings and loan information system designed aims to build a computerized information system to make it easier for employee cooperatives in the Syariah Mandiri Fund employee cooperative in managing member data, savings data, loan data, application data.